Evaluating the effect of business innovation and digital transformation on business resilience during the COVID-19 pandemic: A case study on U-Events Services, Inc. - Cho, Sung Phil B. (Animo Repository, 2023)
The Events Management industry was heavily affected by the COVID-19 pandemic, and with the disruptions caused by the pandemic, resilience–particularly Business Resilience, was exhibited by these firms. In this study, the effect of two metrics: 1) Business Innovation, and 2) Digital Transformation on Business Resilience of an Events Management firm in the Philippines will be determined. For the study, the Events Management firm, U-Events, Inc., collaborated with the researchers for the collection of necessary information relating to the described factors for a semi-structured interview and focus group discussion, where information was also collected from an Events Management expert who collaborated with the researchers via a semi-structured interview. Here, both Business Innovation and Digital Transformation were seen to affect Business Resilience. Through the semi-structured interviews, five main themes of major change of platforms, dynamic environments, developing digital resources, learning and development, and social interactions and purposes were prevalent across the participants. A notable finding by the researchers showed that instead of ability and readiness, open innovation was involved in business innovation in this case, and instead of organizational agility, continuous implementation was a factor in digital transformation, where business innovation and digital transformation were seen to affect business resilience.